2011
DOI: 10.1111/j.1365-2834.2010.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among Iranian hospital-based practicing nurses: examining the influence of self-expectation, social interaction and organisational situations

Abstract: Intervention is needed to increase organisational and professional support for nurses. However, highlighting the sacred and spiritual value of the nursing profession, which is rooted in religious values and culture, provides additional reinforcement for enhancing the job satisfaction among this segment of health care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 95 publications
3
37
0
Order By: Relevance
“…This finding is supported by Cortese () and Ravari et al. (), which reported that nurses were satisfied by helping patients and recognition from patients and family members. Likewise, Archibald () and Stuart et al.…”
Section: Discussionsupporting
confidence: 61%
“…This finding is supported by Cortese () and Ravari et al. (), which reported that nurses were satisfied by helping patients and recognition from patients and family members. Likewise, Archibald () and Stuart et al.…”
Section: Discussionsupporting
confidence: 61%
“…Pay and benefits are mentioned in other studies as important components of job satisfaction (Ravari et al. 2011; Sparks et al.…”
Section: Introductionmentioning
confidence: 98%
“…[23] Further, job satisfaction generally acts like a pendulum in which the "self" is the central axis and the "self" can stabilize satisfaction and direct the effect on other variables on staff satisfaction. [30] They further assert that the job satisfaction phenomenon rounds out the individual's self and so it is the nurses themselves that should strive, plan, keep and promote job satisfaction.…”
Section: Correlation Between the Main Subscalesmentioning
confidence: 99%